The development of a fast method for recording schroeder-phase masking functions - Rahmat, Sarah; O'Beirne, Greg (Elsevier, 2015)
Schroeder-phase masking complexes have been used in many psychophysical experiments to examine the phase curvature of cochlear filtering at characteristic frequencies, and other aspects of cochlear nonlinearity. In a normal nonlinear cochlea, changing the “scalar factor” of the Schroeder-phase masker from −1 through 0 to +1 results in a marked difference in the measured masked thresholds, whereas this difference is reduced in ears with damaged outer hair cells. Despite the valuable information it may give, one disadvantage of the Schroeder-phase masking procedure is the length of the test – using the conventional three-alternative forced-choice technique to measure a masking function takes around 45 min for one combination of probe frequency and intensity. As an alternative, we have developed a fast method of recording these functions which uses a Békésy tracking procedure. Testing at 500 Hz in normal hearing participants, we demonstrate that our fast method: i) shows good agreement with the conventional method; ii) shows high test-retest reliability; and iii) shortens the testing time to 8 min.